2003
DOI: 10.1530/eje.0.1490499
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IGF-I levels in monitoring and predicting efficacy during long-term GH treatment of GH-deficient adults

Abstract: Objective: To investigate the effects of long-term GH in GH-deficient adults, as predicted by IGF-I levels. Methods: Patients received GH, 5 mg/kg per day for 1 month and 10 mg/kg per day for another 12-30 months. Changes in body composition, cardiac structure/function, serum lipids and quality of life were measured. Results: There was a significant increase in lean body mass (LBM) (2.21 kg; P , 0.0001) after 6 months, which was sustained throughout treatment. A larger increase occurred in males than females (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
3
13
2
Order By: Relevance
“…Ezzat et al (26) have found in a group of GHD adults that the effects of GH on lipoproteins, cardiac function, and quality of life could not be predicted by changes in IGF-I levels, which were only associated with alterations in LBM, in line with the findings of our study. In a short-term study with a low GH dose (0.5 IU or 0.17 mg/day), Gillberg et al (16) have shown marked biological effects despite the fact that IGF-I levels did not normalize in many of their patients.…”
Section: Discussionsupporting
confidence: 92%
“…Ezzat et al (26) have found in a group of GHD adults that the effects of GH on lipoproteins, cardiac function, and quality of life could not be predicted by changes in IGF-I levels, which were only associated with alterations in LBM, in line with the findings of our study. In a short-term study with a low GH dose (0.5 IU or 0.17 mg/day), Gillberg et al (16) have shown marked biological effects despite the fact that IGF-I levels did not normalize in many of their patients.…”
Section: Discussionsupporting
confidence: 92%
“…Lower BMI at baseline predicted good response in LBM. This finding is in agreement with a previous study, which also demonstrated that patients with the lowest baseline BMI (below the lower quartile, 24.4 kg/m 2 ) benefited the most in terms of progressive and significant increases in LBM (38). Higher BF at baseline was also a weak predictor of good response in LBM.…”
Section: Predictorssupporting
confidence: 92%
“…With the cut-off values at the 60th and 40th percentiles, we had a higher degree of differentiation between the GR and PR response values. Consistent with other studies (37,38), the increase in LBM and decrease in BF were sustained after 12 months of GH replacement. Gender, baseline BMI, and BF were the most important predictors of LBM response to GH therapy.…”
Section: Predictorssupporting
confidence: 91%
See 1 more Smart Citation
“…To date, no data are available to quantify risk of under-treatment of such patients. Moreover, the optimal target IGF-I during GH replacement remains unclear (22,23). In our study, IGF-I levels rose in all patients and three of the four patients who failed to achieve IGF-I levels into the normal range nonetheless achieved substantial increments in IGF-I SDS of between þ 2.53 and þ 7.39 (Fig.…”
Section: Discussionmentioning
confidence: 57%